The Labor Market Effects of Foreign-Owned Firms - Almeida, Rita (World Bank, Washington, D.C., 2013)
Foreign firms often have a more educated workforce and pay higher wages than domestic firms. This does not necessarily imply that foreign ownership translates into higher demand for educated workers or higher wages, since foreign investment may be guided by unobservable firm characteristics correlated with the demand for educated workers or wages. The author examines foreign acquisitions of domestic firms in Portugal in the 1990s and finds small changes in the workforce skill composition and wages following acquisition. Foreign investors "cherry pick" domestic firms that are already very similar to the group of existing foreign firms.